Author response: Calcium supplementation and risk of dementia in women with cerebrovascular disease. (21st February 2017) - Kern, Silke; Kern, Jürgen; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Guo, Xinxin; Börjesson-Hanson, Anne; Skoog, Ingmar; Östling, Svante
Abstract : We thank Drs. Rosenberg and Beale for the interesting comments on our article. 1